Tokwa maker / Nurul Huda Abdul Azid ...[et al.] - Abdul Azid, Nurul Huda; Jebat, Nurul Azuwa; Norafandi, Rabl'atul Adawiyah; Jasmin, Nursyafiqah (2016)
Soy milk has been produced traditionally in China, and started to be introduced elsewhere in East Asia especially in Malaysia. Varieties of benefits are obtained in soy milk such as high in fiber, protein and have cholesterol free. Nevertheless, currently, the available traditional soy milk machines have difficulties in producing good quality of soy milk. One of the reasons is the machine need to be operated by human power. This eventually will result in human fatigue especially in the process of pressing concentrated soy milk. In order to solve the above mention problem, Tokwa Maker, the revolutionised tofu machine is introduced. The aims for this machine are to reduce the usage of human power as well as to invent a new method in identifying the compactness of tofu. The machine used a semi-automatic stamping mechanism for the purpose of maintaining a good quality tofu. A total of 64 pieces of tofu per process can be produce.